From final judgment to final resolution : effectiveness of the execution of judgments of the European Court of human rights in Finland - Heikkilä, Satu (Oisterwijk : Wolf Legal Publishers, 2016)
D'un arrêt définitif à une résolution finale : l'efficacité de l'exécution des arrêts de la Cour européenne des droits de l'homme en Finlande.
Väitöskirja
Keywords: Euroopan ihmisoikeustuomioistuin; kansainvälinen oikeus; kansainväliset tuomioistuimet; tuomiot; täytäntöönpano; tehokkuus; Suomi